Frequency of Hepatitis B, C and HIV Infections among Transfusion-Dependent Beta Thalassemia Patients in Dhaka - Golam Sarower Bhuyan; Aftab Uz Zaman Noor; Rosy Sultana; Farjana Akther Noor; Nusrat Sultana; Suprovath Kumar Sarker; Muhammad Tarikul Islam; Md. Abu Sayeed; Md. Imam Ul Khabir; A. K. M. Ekramul Hossain; Zebunnesa Zeba; Syeda Kashfi Qadri; et al. (MDPI AG, 2021)
Transfusion transmitted infections have remained a major deterrent to public health, particularly among the patients with transfusion-dependent Beta thalassemia in developing countries. Although proper donor selection through adoption of WHO-advised infection panel has lowered the rate of infections, the multi-transfused patients are not free of risk. In this study, we screened 148 transfusion-dependent Beta thalassemia patients to determine the frequency of Hepatitis C Virus (HCV), Hepatitis B Virus (HBV) and Human Immunodeficiency Virus (HIV) using the ELISA method. Among them, infected cases with HCV, HBV and HIV were 13.51%, 3.37% and 0%, respectively. Moreover, 2% of the patients were found to be co-infected with both HBV and HCV. The percentage of infections in the patients with frequent transfusion interval (≤30 days) was significantly higher (p < 0.0005) than that in the patients with less frequent transfusion intervals (>30 days). Immunochromatography (ICT)-based rapid test kits are usually used to screen and confirm these infections in the blood of the patients. However, ICT-based tests are not sensitive enough to detect the infections. So, a combination of both Nucleic Acid testing (NAT) and serological testing are suggested to significantly reduce the risk of viral infections during blood transfusion.